The relationship between work family conflict and job performance at University Teknologi Mara Campus Jengka, Pahang / Nursyafiqa Fatin Hassan - Hassan, Nursyafiqa Fatin (Faculty of Business Management, 2017)
The topic that choose was to study the relationship between family conflict and job performance among non-academic staffs in the University Teknologi MARA (UiTM) Jengka,Pahang. The questionnaire was being distributed and used as instrument to collect the data that needed in order to complete this research and used as instrument to collect the data that needed in order to complete this research paper. The data that had been collected were analysed via IBM SPSS Statistics 21.0 software. There are 7 staff from non-academic that are been chosen as the respondent. This research paper convenience sampling. Based on the findings, there is significant relationship between work family conflict and job performance which is work to family conflict (r=.017,n=75)but it was weak relationship. Meanwhile ,family to work conflict (r=019,n=75) which is also significant relationship but have weak relationship. For the cooperative strategy (r=.147, n=75)was not significant relationship and also have negative and weak relationship .There are some recommendations that can be implementing by UiTM Jengka to improve the job performance of the employees. Other than that ,the researcher for future research should conduct study at other industry other than education industry to find the variety of the finding in their research